K-Means clustering untuk pengelompokan daerah penghasil padi di Indonesia berdasarkan luas panen, produksi, dan produktivitas padi tahun 2022 - Putri, Erika Ayu Prastia (Maliki Interdisciplinary Journal, 2024)
Rice plants are one of the main crops for fulfilling the food needs of the Indonesian people. Out of the 10.61 million hectares of land in Indonesia, used for agriculture, rice cultivation covers a significant portion, and the government hopes to meet the food needs of the entire population. Each region in Indonesia has different rice harvest areas, production, and productivity levels. Some areas produce a considerable amount of rice, while others do not. Based on this issue, we can divide the regions in Indonesia into several categories of rice-producing areas. This clustering will form three clusters, namely: (1) Cluster 1, the Largest Rice-Producing Region, (2) Cluster 2, the Intermediate Rice-Producing Region, and (3) Cluster 3, the Lowest Rice-Producing Region. The cluster calculation is performed using the K-Mean algorithm with Minitab software, and the visualization is presented in a 3D Scatterplot.